2013
DOI: 10.1002/2013gc004870
|View full text |Cite
|
Sign up to set email alerts
|

A controlled‐source seismic and gravity study of the High Lava Plains (HLP) of Eastern Oregon

Abstract: [1] This study employs data collected during the High Lava Plains (HLP) controlled-source seismic experiment conducted in September 2008. In this experiment, 2612 short-period seismic recorders and 120 3-component recorders were deployed across eastern Oregon and adjacent parts of Nevada and Idaho to record 15 seismic sources. Seismic and gravity data were integrated to create 2-D crustal scale P-wave velocity and density models for the 400 km long NW-SE and N-S profiles to provide a better understanding of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…The one dome that does crop out within this age range is Burns Butte, located on the northern edge of the Harney Basin (Figure 3d), where subsidence would be minimal. Recent geophysical studies [Cox, 2011] indicate volcanic rocks and sediments may extend to as deep as 7 km in the Harney Basin, at least 2 km deeper than other places in the HLP or Basin and Range. Well logs from the eastern part of the Harney Basin indicate 0.75 to more than 1.5 km of sediment [Milliard, 2010].…”
Section: Subsidence Of the Hlp And Effects On Rhyolite Outcrop Distrimentioning
confidence: 99%
See 1 more Smart Citation
“…The one dome that does crop out within this age range is Burns Butte, located on the northern edge of the Harney Basin (Figure 3d), where subsidence would be minimal. Recent geophysical studies [Cox, 2011] indicate volcanic rocks and sediments may extend to as deep as 7 km in the Harney Basin, at least 2 km deeper than other places in the HLP or Basin and Range. Well logs from the eastern part of the Harney Basin indicate 0.75 to more than 1.5 km of sediment [Milliard, 2010].…”
Section: Subsidence Of the Hlp And Effects On Rhyolite Outcrop Distrimentioning
confidence: 99%
“…Logs from a few energy exploration drill holes indicate that intercalated sediments and ''Miocene and younger'' undifferentiated volcanic rocks extend to depths of >1.5 km within the Harney Basin in the HLP [Milliard, 2010] and >3.5 km west of Lakeview in the NWBR [Popenoe, 1961;Newton et al, 1962]. Recent geophysical studies [Cox, 2011] indicate that Cenozoic intercalated sediments and volcanic rocks may be >7 km thick in the eastern Harney Basin, which is likely the locus of calderas for the Devine Canyon and PCTs. Field work and previous studies (see later) have indicated that the 12-0 Ma volcanic rocks generally make up only a thin veneer where exposed, and while the Harney Basin may have appreciable volumes of these younger rocks, we consider it more likely that the basin contains mostly sediments and volcaniclastic rocks with only a limited volume of <12 Ma basalts and rhyolites.…”
mentioning
confidence: 99%
“…Egger et al (2010) investigated the structural controls on the Surprise Valley extensional basin in northeastern California by integrating geologic mapping with 2D potential field and seismic velocity modeling. Cox et al (2013) studied the crustal structure and tectonic evolution of the High Lava Plains region of eastern Oregon through an integration of seismic, gravity, and geologic information. Khatiwada and Keller (2015) focused on the Harney Basin of the High Lava Plains region and employed geologic, gravity, magnetic, digital elevation, and other geospatial data to execute an integrated geoscience study.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The 2008 HLP active seismic data set has been analyzed previously (e.g., Okure, 2009;Cox et al, 2013) and interpreted in the form of 2D seismic lines. Okure (2009) used the HLP seismic data around the Harney Basin area and tentatively located the basin boundary based on the travel-time delays observed in the seismic data.…”
Section: The High Lava Plains Active Source Seismic Experimentsmentioning
confidence: 99%
“…In the HLP, the time-transgressive Cenozoic volcanic activity covered the area with lava fl ows and pyroclastic material (e.g., Camp and Ross, 2004;Brueseke et al, 2007;Streck and Grunder, 2008), making it diffi cult to identify older crustal structures and decipher tectonic events (Anderson, 1989). Thus, the HLP was the focus of a large project funded by the National Science Foundation, which involved a wide range of geophysical and geological studies that helped resolve the crustal structure of the crust and upper mantle (e.g., Roth et al, 2008;West et al, 2009;Eagar et al, 2010Eagar et al, , 2011Druken et al, 2011;Cox et al, 2013).…”
Section: Introductionmentioning
confidence: 99%